Tinjauan Campuran Bahan Bakar Etanol dan Pertamax dengan Bahan Bakar Pertalite Terhadap Emisi Gas Buang pada Sepeda Motor - SURBAKTI, ADNAN (Journal of Engineering and Information Technology for Community Service, 2024)
The purpose of this research is to differentiate exhaust emissions (CO and HC) of a motorcycle fueled by a mixture of firstx and ethanol (95-5%) with pertalie fuel. The method used is the expriment method, namely by conducting direct experiments. The materials and tools used are a supra x 125 motorcycle, gas analyzer, firstx, ethanol, pertalite. The results of the study were obtained for a mixture of firstx and ethanol (95-5%) for a rotation of 1000 rpm, the CO price was 0.67%, and the HC price was 203 ppm, for a rotation of 2000 rpm the CO price was 0.47%, and the HC price was 188.3 ppm, for a rotation of 3000 rpm the CO price was 0.27%, and the HC price was 87.6 ppm. In conclusion, the higher the rotation, the greater the HC of both the firstx and ethanol mixture and the premium price is smaller, while for CO, if the rotation is greater, the percentage is smaller for the firstx and ethanol mixture, and the premium price is greater.